Effect of porous baffle on sloshing pressure distribution in a barge mounted container subjected to regular wave excitation (Journal of Naval Architecture and Marine Engineering, 2020)
An experimental study has been carried out to assess the sloshing pressure expected on the side walls of the tank and on top panel. A liquid fill level with an aspect ratio (hs /l, where hs is the static liquid depth and l is the tank length) of 0.488 is considered which corresponds to 75% liquid fill level. In view of suppressing sloshing oscillation and consequent sloshing pressure, the baffle wall configurations such as porous wall at l/2 and porous walls at l/3 and 2l/3 were adopted. Three porosities of 15%, 20.2%, and 25.2% were considered. The sloshing tank is fitted into the freely floating barge of model scale 1:43. The barge is kept inside the wave flume in the beam sea conditions. The effects of wave excitation frequencies and on the sloshing pressure variation have been studied in detail. For comparison purpose, solid wall placed at l/2 (Nasar and Sannasiraj, 2018) is also considered and, the salient results are herein reported.